Comparative morphology and morphometry of the mesencephalic tectum in the African giant rat (Cricetomys gambianus). (30th July 2022) - Ogbonnaya, Obioma; Ibe, Samuel Chikera; Ikpegbu, Ekele
Abstract: The caudal colliculus serves as an integrative station and switchboard, controlling nucleus of lower auditory pathway and motor‐auditory reflex production. The rostral colliculus coordinates reflexive movement of the head, neck, eye and focus the lens for visual tracking of objects. There is no information comparing mesencephalic tectum among neonates, juveniles and adults of African giant rat (AGR). Hence, this study aimed to compare the gross features and morphometric parameters of mesencephalic tectum postnatally in AGR. The following were found and reported: (a) Paired dorsal tips of caudal colliculi were observed through transverse fissure of the intact brain and so, corpora quadrigemina were partly occluded by cerebral cortex in neonates and juveniles. (b) The lateral and medial geniculate bodies were visible, though the lateral was grossly bigger than the medial in adults and juveniles but,   only the lateral was distinguishable in neonates. (c) Live body weight, absolute brain weight, caudal colliculus width, nose–rump and tail lengths increased as AGRs developed with age; mean values of rostral colliculus weight, caudal colliculus height and weight of caudal colliculus in neonates and juveniles were statistically same; while midbrain weight and rostral colliculus height tends to decrease as rats aged. (d) The mean weight of caudal colliculi and width of rostral colliculi were not affected by age. (e) Caudal colliculi were grossly wider than rostral in juveniles and adults, but not neonates. Established regression formulae are necessary to avoid future sacrifice of this rodent.